Effective justice in criminal proceedings (A comparative analytical study) - Faraj, Dr.Sirwan Othman Faraj; Saleh, Asst.Prof.Dr.Rizkar Abdul Karim Saleh (Sulaimani Journal for Humanities, 2025)
The aim of implementing a system of expedited justice in criminal proceedings is to ensure that every individual receives their due rights fairly and within a reasonable timeframe. Although the Iraqi criminal legislator has not used the term "expedited justice," it nevertheless seeks, through the enactment of the Code of Criminal Procedure, to establish a set of legal rules that embody the swift resolution of criminal cases. These legal rules, in their entirety, constitute aspects of expedited criminal justice. Some of these aspects pertain to the pre-trial stage of criminal proceedings, some to the trial stage, and the remainder to the post-trial stage. Undoubtedly, a system of expedited justice in criminal proceedings in Iraq requires legislative reforms and the adoption of best practices from comparable legal systems.
Keywords: The aim of implementing a system of expeditious justice in criminal proceedings is to ensure that every individual receives their due rights fairly and within a reasonable timeframe Although the Iraqi criminal legislator has not used the term expeditious justice; it nevertheless seeks; through the enactment of the Code of Criminal Procedure; to establish a set of legal rules that embody the swift resolution of criminal cases These legal rules; in their entirety; constitute the manifestations of expeditious criminal justice Some of these manifestations pertain to the pretrial stage of criminal proceedings; some to the trial stage; and the remainder to the posttrial stage Undoubtedly; the system of expeditious justice in criminal proceedings in Iraq requires legislative reforms and the adoption of best practices from comparable legal systems